Enhanced vision based vein detection system - Ahmed, Kazi Istiaque; Habaebi, Mohamed Hadi; Islam, Md. Rafiqul; Zainal, Nur Aishah (IEEE, 2018)
The process of needle infusion is done daily endless times everywhere and even though it is simple procedure the sheer number of erroneous procedures that can be serious and fatal for the patient is attentive. To prevent or at least reduce the number of errors, this paper proposes an easy guiding method for nurse and doctors to be integrated into the procedure. A vision-based imaging technique, that gives a practitioner a new perspective for the needle infusion procedure, is introduced. The idea behind of this process is to use the IR camera to capture video sequences of the arm and then compute the effect of electromagnetic wave imprint on each pixel. Then trace the vein location by locating the NIR illumination that is absorbed by the blood in the vein and highlighting it in comparison to the surrounding tissue. Interestingly, this can lead to other applications for the developed system like locating abdominal bleeding, stroke inducing clots in veins near the skin surface and body part vein map-based individual identification biometric to name a few.